Eccentric exercise increases circulating fibroblast activation protein α but not bioactive fibroblast growth factor 21 in healthy humans. Issue 6 (31st May 2018) - Parmar, Biraj; Lewis, Jo E.; Samms, Ricardo J.; Ebling, Francis J. P.; Cheng, Christine C.; Adams, Andrew C.; Mallinson, Joanne; Cooper, Scott; Taylor, Tariq; Ghasemi, Reza; Stephens, Francis B.; Tsintzas, Kostas
Abstract : New Findings: What is the central question of this study? The role of FGF21 as an exercise‐induced myokine remains controversial. The aim of this study was to determine whether eccentric exercise would augment the release of FGF21 and/or its regulatory enzyme, fibroblast activation protein α (FAP), from skeletal muscle tissue into the systemic circulation of healthy human volunteers. What is the main finding and its importance? Eccentric exercise does not release total or bioactive FGF21 from human skeletal muscle. However, exercise releases its regulatory enzyme, FAP, from tissue(s) other than muscle, which might play a role in the inactivation of FGF21. Abstract: The primary aim of the investigation was to determine whether eccentric exercise would augment the release of the myokine fibroblast growth factor 21 (FGF21) and/or its regulatory enzyme, fibroblast activation protein α (FAP), from skeletal muscle tissue into the systemic circulation of healthy human volunteers. Physically active young healthy male volunteers (age 25.0 ± 10.7 years; body mass index 23.1 ± 7.9 kg m −2 ) completed three sets of 25 repetitions (with 5 min rest in between) of single‐leg maximal eccentric contractions using their non‐dominant leg, whilst the dominant leg served as a control. Arterialized blood samples from a hand vein and deep venous blood samples from the common femoral vein of the exercised leg, along with blood flow of the superficial femoral artery using Doppler ultrasound, were obtained before and after each exercise bout and every 20 min during the 3 h recovery period. Muscle biopsy samples were taken at baseline, immediately and 3 and 48 h postexercise. The main findings showed that there was no significant increase in total or bioactive FGF21 secreted from skeletal muscle into the systemic circulation in response to exercise. Furthermore, skeletal muscle FGF21 protein content was unchanged in response to exercise. However, there was a significant increase in arterialized and venous FAP concentrations, with no apparent contribution to its release from the exercised leg. These findings raise the possibility that the elevated levels of FAP might play a role in the inactivation of FGF21 during exercise. Abstract :